The stoic origins of Erasmus' philosophy of Christ - Dealy, Ross (University of Toronto Press, 2017)
"This study focuses on Erasmus' two-dimensional grasp of Stoicism evident in his edition of De officiis (1501) and the huge implications he saw for religion. The author argues that "The Philosophy of Christ' for which Erasmus is famous is a Christian version of Stoicism."-- Provided by publisher
Keywords: Erasmus, Desiderius, -- -1536 -- Criticism and interpretation.; Jesus Christ.; Érasme, -- -1536 -- Critique et interprétation.; Jésus-Christ.; Erasmus, Desiderius, -- -1536; Jesus Christ; Stoics.; Stoïcisme.; stoicism.; PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- History & Surveys -- Renaissance.; Stoics; Criticism, interpretation, etc.